Răspuns:
Explicație pas cu pas:
a) 0,9⁵ · 0,9³ = 0,9⁵⁺³ = 0,9⁸
b) (9/25)ᵃ : (3/5)ᵇ = (3/5)³ <=>
[(3/5)²]ᵃ ·(5/3)ᵇ = (3/5)³ <=>
(3/5)²ᵃ ·(5/3)ᵇ = (3/5)³ <=>
(3/5)²ᵃ⁻ᵇ = (3/5)³ =>
2a - b = 3 => b = 2a-3
a = 0 => b = -3
a = 1 => b = -1
a = 2 => b = 1
a = 3 => b = 3
a = 4 => b = 5 ; etc ..........................etc
-------------------
Exemple (verificare)
a = 3 ; b = 3 =>
(9/25)³ : (3/5)³ = [(3/5)²]³ : (3/5)³ = (3/5)²ˣ³ : (3/5)³ =
= (3/5)⁶⁻³ = (3/5)³ ; corect
a = 4 => b = 5
(9/25)⁴ : (3/5)⁵ = [(3/5)²]⁴ : (3/5)⁵ =
= (3/5)²ˣ⁴ : (3/5)⁵ = (3/5)⁸⁻⁵ = (3/5)³ corect